2015
DOI: 10.1038/srep17367
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of the 11q23.3 glioma susceptibility locus implicates PHLDB1 and DDX6 in glioma susceptibility

Abstract: Glioma is the most common malignant primary brain tumor and is associated with poor prognosis. Genetic factors contributing to glioma risk have recently been investigated through genome-wide association studies (GWAS), implicating seven independent glioma risk loci in six chromosomal regions. Here, we performed an in-depth functional analysis of the risk locus proximal to the PHLDB1 gene on 11q23.3. We retrieved all SNPs in linkage disequilibrium (r2 ≥ 0.2) with the glioma-associated SNP (rs498872) and perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…111,112 Inherited Factors Genome-wide association studies have identified several genetic loci associated with increased risk of glioma, including TERT, CDKN2A/2B, RTEL1, PHLDB1, EGFR, TP53, TERC, DDX6, and PIWI-interacting RNAs. [113][114][115] Of these genes, TERT, CDKN2A/2B, EGFR, and TP53 are wellcharacterized recurrently altered genes in sporadic IGs. In addition to well-known inherited tumor syndromes, such as Li Fraumeni, the study of familial cases of IG remains an important avenue toward identifying genetic candidates that drive glioma formation.…”
Section: Selected Environmental Factorsmentioning
confidence: 99%
“…111,112 Inherited Factors Genome-wide association studies have identified several genetic loci associated with increased risk of glioma, including TERT, CDKN2A/2B, RTEL1, PHLDB1, EGFR, TP53, TERC, DDX6, and PIWI-interacting RNAs. [113][114][115] Of these genes, TERT, CDKN2A/2B, EGFR, and TP53 are wellcharacterized recurrently altered genes in sporadic IGs. In addition to well-known inherited tumor syndromes, such as Li Fraumeni, the study of familial cases of IG remains an important avenue toward identifying genetic candidates that drive glioma formation.…”
Section: Selected Environmental Factorsmentioning
confidence: 99%
“…In addition, PHLDB1 can bind PI (3, 4, 5) P3 through its PH domain in adipocytes and function as a positive regulator of Akt activation by insulin16. More recent studies171819 have shown the correlation between PHLDB1 SNPs and glioma risk, implicating that PHLDB1 may play a potential role in the development of glioma. Noteworthily, PHLDA3, one of the pleckstrin homology-like domain family A proteins, was previously reported as a direct target gene of p53 (ref.…”
mentioning
confidence: 99%
“…Nuclear extracts were obtained from iOSE4 CMYC cells at 70%-90% confluence and electrophoretic mobility shift assays (EMSA) were run as described previously (18).…”
Section: Electrophoretic Mobility Shift Assaysmentioning
confidence: 99%